2022
DOI: 10.1101/2022.02.09.479693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single dose of the catecholamine precursor Tyrosine reduces physiological arousal and decreases decision thresholds in reinforcement learning and temporal discounting

Abstract: Supplementation with the catecholamine precursor L-Tyrosine might enhance cognitive performance, but overall findings are mixed. Here, we investigate the effect of a single dose of tyrosine (2g) vs. placebo on two key aspects of catecholamine-dependent decision-making: model-based reinforcement learning (2-step task) and temporal discounting, using a double-blind, placebo-controlled, within-subject design (n=28 healthy male participants). We leveraged drift diffusion models in a hierarchical Bayesian framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 129 publications
0
10
1
Order By: Relevance
“…via L-Dopa or Haloperidol) intake modulates both model-based control (Wunderlich et al, 2010; Sharp et al, 2016) and temporal discounting (de Wit et al, 2002; Pine et al, 2010; Wagner et al, 2020). Recently, we found that a single dose of the catecholamine precursor L-Tyrosine resulted in faster response times in both tasks due to reduced decision thresholds according to DDM (Mathar et al, 2022). However, the findings regarding dopaminergic manipulation of both model-based control (Kroemer et al, 2019; Deserno et al, 2021) and delay discounting (Petzold et al, 2019) are still heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…via L-Dopa or Haloperidol) intake modulates both model-based control (Wunderlich et al, 2010; Sharp et al, 2016) and temporal discounting (de Wit et al, 2002; Pine et al, 2010; Wagner et al, 2020). Recently, we found that a single dose of the catecholamine precursor L-Tyrosine resulted in faster response times in both tasks due to reduced decision thresholds according to DDM (Mathar et al, 2022). However, the findings regarding dopaminergic manipulation of both model-based control (Kroemer et al, 2019; Deserno et al, 2021) and delay discounting (Petzold et al, 2019) are still heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Based on suggestions by Kool et al (2016) we modified the outcome stage by replacing the fluctuating reward probabilities (reward / no reward) with fluctuating reward magnitudes (Gaussian random walks with reflecting boundaries at 0 and 100, and standard deviation of 2.5). This task version has been successfully applied in a number of recent papers from our group (Mathar et al, 2022; Wagner et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by the authors, this might also be due to dose-dependent presynaptic effects of Bromocriptine, which might have resulted in a net reduction in DA transmission 53 . But another possibility is that DA might specifically contribute to threshold adjustments in value-based decision settings 51 . This idea resonates with the role of dopamine in regulating response vigor [34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, increased DA availability in mice increases response rates in the absence of learning 50 , again consistent with a threshold reduction. In humans, administration of the catecholamine precursor tyrosine reduces decision thresholds across different value-based decision-making tasks 51 , and the DA agonist ropinirole reduces decision thresholds during inhibition 52 . In contrast, Bromocriptine (a DA agonist) does not affect thresholds during perceptual decision-making 53 , suggesting that such effects might be task dependent.…”
Section: Introductionmentioning
confidence: 99%